ANALISIS PENGARUH PERINGKAT, MATURITAS, DAN KUPON OBLIGASI TERHADAP HARGA OBLIGASI DI BURSA EFEK INDONESIA - B2042162016, TRI YANTI (Equator Journal of Management and Entrepreneurship (EJME), 2019)
ABSTRACT This research is intented to find out the influences of rank, maturity, and obligation coupon towards obligation value on Indonesia Stock Exchange. Purposive sampling method is used for the sample criteria. The population in this research is a corporation’s obligation per year from 2012-2016. The data is analysed using multiple linear regression. Based on the results of the analysis data, it is indicated that the rate in 2012 has positive and significant effects on the obligation value, the rate in 2013 has negative and insignificant effects on the obligation value. The rates in 2014 and 2016 have negative and significant effects on the obligation value. And the rate in 2015 has positive and insignificant effects on the obligation value. The maturity in 2012 and 2016 have positive and significant effects on the obligation value. The maturity in 2013 and 2014 have negative and significant effects on the obligation value. The maturity in 2015 has negative and insignificant effects on the obligation value. Obligation coupon in 2012,2014,2015,2016 have negative and insignificant effects on the obligation value. The obligation coupon in 2013 has negative and insignificant effects on the obligation value.                     Keywords: Rate, Maturity, Obligation Coupon, Obligation value, and Multiple Linear Regression